3D intra-cellular wave dynamics in a phononic plate with ultra-wide bandgap: attenuation, resonance and mode conversion. (2nd February 2022) - Hedayatrasa, Saeid; Kersemans, Mathias
Abstract: The intra-cellular wave dynamics of a water jetted phononic plate are experimentally investigated by means of high-resolution three-dimensional (3D) scanning laser Doppler vibrometry. The study is focused on the vibrational behavior around the ultra-wide bandgap of the plate (with a relative bandgap width of 0.89), as the critical frequency range of its phononic functionality. Broadband vibrational excitations are applied using a piezoelectric transducer and both in-plane and out-of-plane operational deflection shapes of the unit-cells are analyzed with respect to mode shapes calculated by finite element (FE) simulation. Attenuation and resonance of both symmetric and antisymmetric wave modes are validated, and it is shown that despite the absence of in-plane wave energy actuation, the symmetric modes are effectively excited in the phononic lattice, due to mode conversion from co-existing antisymmetric modes. Supported by FE modal analysis, this mode conversion observation is explained by the slight through-the-thickness asymmetry introduced during manufacturing of the phononic plate which leads to coupling of modes with different symmetry. The results confirm the potential of such detailed 3D inspection of phononic crystals (and in general acoustic metamaterials) in gaining full insight about their intracellular dynamics, which can also illuminate discrepancies with respect to idealized numerical models that might be due to manufacturing imperfections.